2021
DOI: 10.3389/fimmu.2021.679482
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 ORF8 Forms Intracellular Aggregates and Inhibits IFNγ-Induced Antiviral Gene Expression in Human Lung Epithelial Cells

Abstract: Infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes COVID-19, a disease that involves significant lung tissue damage. How SARS-CoV-2 infection leads to lung injury remains elusive. The open reading frame 8 (ORF8) protein of SARS-CoV-2 (ORF8SARS-CoV-2) is a unique accessory protein, yet little is known about its cellular function. We examined the cellular distribution of ORF8SARS-CoV-2 and its role in the regulation of human lung epithelial cell proliferation and antiviral imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 57 publications
1
55
1
Order By: Relevance
“…Deletion of ORF8 leads to decreased severity of infection as reported [27,46]. ORF8 is also involved in suppression antiviral proteins from INFγ [14]. SARS-CoV-2 drug or vaccines were using spike protein as an important target [20,37,38,41], but ORF8 can be also targeted for producing therapeutic approaches.…”
Section: Introductionmentioning
confidence: 97%
“…Deletion of ORF8 leads to decreased severity of infection as reported [27,46]. ORF8 is also involved in suppression antiviral proteins from INFγ [14]. SARS-CoV-2 drug or vaccines were using spike protein as an important target [20,37,38,41], but ORF8 can be also targeted for producing therapeutic approaches.…”
Section: Introductionmentioning
confidence: 97%
“…We also identify mutational hotspots in the 3′-to-5′ exonuclease, endoRNAase, 2′-O-Ribose methyltransferase, Spike protein, ORF7a/b, and ORF8. Mutations in some regions have been linked to host functional alterations such as the role of ORF7a in host immune suppression 30 and ORF8’s role in intracellular stress pathways 31 , 32 . Functional roles of other viral mutations remain to be characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro evidence suggests that ORF8 may have more roles in immune evasion as previously described. Its ectopic expression has been correlated with a reduced expression of several IFNγ-induced antiviral molecules with different biochemical activities in lung epithelial cells (311). Interestingly, the same group observed that ectopic expression of ORF8 in HEK293 cells reduced the expression of different antiviral proteins, suggesting that the effects of ORF8 on ISGs may be cell type specific.…”
Section: Other Interactions Contributing To Immune Evasion By Sars-cov-2mentioning
confidence: 96%